Critics as "bricoleurs": some remarks - Catelli, Nora (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
What is the relationship between Theory and Comparative and World Literature; how is that link thought? And, in my case, what are the objects on which we work, taking into account this difficult crossing today? I pick up these questions for this dialogue with Túa Blesa, which gives them a renewed and, perhaps, lighter meaning.